2018
DOI: 10.1111/jen.12569
|View full text |Cite
|
Sign up to set email alerts
|

Formicidal activity of indole derivatives on Atta opaciceps (Borgmeier): Lethal, behavioural and locomotive effects

Abstract: The leaf‐cutting ants of the genus Atta are of extreme importance for agriculture and forestry. Few active products can be employed to control these pests and, therefore, the discovery of new insecticidal products represents a fundamental strategy for its management. In this study, we evaluated the mortality, behaviour and locomotion of workers of Atta opaciceps (Borgmeier) exposed to synthesized indole derivatives. The most active compound was 4d [1‐(1H‐indol‐3‐yl)pentan‐1‐one] (LD50 = 0.018 μg/mg), while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Indoles are a class of alkaloids best avoided by invertebrate and vertebrate predators alike, as their effects are deleterious and can extend to behavioural modi cations. Indole derivatives, for example, increase mortality (likely through neurotoxic activity) in ants (Costa et al 2019), which are important predators of caterpillars in tropical forests (Sam et al 2015). Indoles are also widely employed as signalling molecules and are able to counter viral and bacterial pathogens (Lee et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indoles are a class of alkaloids best avoided by invertebrate and vertebrate predators alike, as their effects are deleterious and can extend to behavioural modi cations. Indole derivatives, for example, increase mortality (likely through neurotoxic activity) in ants (Costa et al 2019), which are important predators of caterpillars in tropical forests (Sam et al 2015). Indoles are also widely employed as signalling molecules and are able to counter viral and bacterial pathogens (Lee et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that altering a parent molecule can cause changes in the bioactivity of compounds [8,21,23]. In the present study, we synthesized new molecules derived from thymol and evaluated the bioactivity of these compounds on leaf-cutting ants.…”
Section: Discussionmentioning
confidence: 96%
“…One of the difficulties in controlling leaf-cutting ants, for example, is the lack of knowledge about their complex social structure, in addition to their collective defenses (e.g., prophylactic behaviors) that can reduce control efficiency [3,4]. Behaviors carried out among ants such as cleaning, trophallaxis and other types of physical contact, such as antennation [5,6], can contribute to a faster distribution of insecticides within the colony [7,8].…”
Section: Of 17mentioning
confidence: 99%
“…The indole skeleton is an aromatic heterocyclic ring and is widely found in natural products, including different kinds of plants, animals, and marine organisms. It can bind with a variety of receptors, and indole derivatives have various biological activities, such as insecticidal, , antiviral, , antibacterial activities . In this study, the natural product indole was introduced into part C of the mesoionic pyridopyrimidine ring and conjugated with it, and a series of novel mesoionic derivatives were synthesized (Figure ).…”
Section: Introductionmentioning
confidence: 99%